Type 1 insulin-like growth factor receptor targeted therapies in pediatric cancer - Wagner, Michael J.; Maki, Robert G. (Frontiers in Oncology, 2013)
Data from over 20 years ago demonstrated potential use for IGF signaling modulators, specifically with IGF-1R antagonists, in a variety of pediatric and adolescent cancers, particularly in sarcomas. However, in spite of promising preclinical data, IGF-1R inhibitors have not had the success as single agents that was originally hoped for in clinical trials. Several potential mechanisms exist by which tumors are resistant to IGF-1R inhibitors. Notably, these resistance mechanisms are currently best understood in Ewing sarcoma and alveolar rhabdomyosarcoma. Various treatment schema have been proposed as a potential way to overcome this resistance. The use of IGF-1R inhibitors, mechanisms of resistance, and current ongoing clinical studies using IGF-1R inhibitors in pediatric cancers are reviewed here.